Physical activity in students and its association with attention. A systematic review - Jaime Eduardo Alvarado Melo; Henry Humberto Leon-Ariza; Erika Viviana Ladino Marin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Despite the recommendations for physical activity in children and adolescents, sedentary behaviors that may affect health are frequent in today's schools. Evidence suggests that physical activity has a beneficial effect on the development of attention, however, there is no clarity on the characteristics that physical activity should have to optimize the improvement of attention in schoolchildren. A search for articles in databases published between 2013 and 2023 was performed, and after applying the inclusion and exclusion criteria and after analyzing their results, thirty-three articles were identified. The results suggest that the practice of physical activity has a positive effect on attention, mainly selective attention, but it is not possible to establish the characteristics in relation to frequency, time, intensity, or type of exercise that yield the best results, probably due to the heterogeneity of the interventions and populations studied. More experimental studies are therefore required to help identify the characteristics of physical activity that best contribute to the development of attention as a cognitive indicator.